Pelatihan Pembuatan LIPBALM dari Bahan yang Aman untuk Kesehatan - Gusmarwani, Sri Rahayu (LPPMI Institut Teknologi Nasional Yogyakarta, 2025)
Awareness increasing of health and environmental sustainability is the background to the choice of natural lip balm which is certainly healthier and more responsible for users. Hazardous chemicals that used in cosmetic products were still not widely understood by the public, so it was necessary to socialize the use of chemicals that were safe for health as well as how to make them. Natural lip balm was needed for several main reasons, including: safety and health, naturally moisturizing, avoiding the risk of allergies and irritation, environmentally friendly, additional nutrition for the lips, does not contain toxic ingredients. Lip balm training activity was carried out as part of community service activities that are members of the GaGeGo Organic (3GO) community in Pati Regency, Central Java. The benchmark for the success of the activity could be seen from the number of participants who attended, the questions asked, and the activeness of participants during the lecture (explanation) and practice. The questions were grouped into 5, namely: The importance of natural lip balm and its effects on the user's body, lip balm ingredients, equipment, manufacturing methods, and economic calculations for sales. The challenge experienced during the implementation of the service was the duration of the training time was too short so that the explanation was done while practicing.